Kemajemukan peserta didik untuk mencapai target kurikulum dengan pembelajaran berdiferensiasi: Refleksi keberagaman peserta didik di kelas - Rofiqi, Ainur (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2025)
The research aims to describe the plurality of learners in achieving curriculum targets through differentiated learning as a reflection of the diversity of learners in the classroom. The research method is a literature study by reading books or journal articles. The results show that differentiated learning has a positive impact on students in optimizing learning outcomes to achieve curriculum targets as needed through differentiation of content, process, product, and learning environment. Differentiated learning strategies can be developed by differentiating learners based on blood type, music genre, zodiac / Javanese platoon, graphology, birth order, and others. The conclusion of this research is that every learner is not the same as other learners, the plurality of learners is of course already there from the outside so it must be in accordance with the nature of nature and the nature of their time, so differentiated learning is needed in education.   Tujuan penelitian mendeskripsikan kemajemukan peserta didik dalam mencapai target kurikulum melalui pembelajaran berdiferensiasi sebagai refleksi keragaman peserta didik di kelas. Metode penelitian yaitu studi kepustakaan dengan membaca buku atau artikel jurnal. Hasil penelitian menunjukkan pembelajaran berdiferensiasi berdampak positif bagi peserta didik dalam optimalisasi hasil belajar untuk mencapai target kurikulum sesuai kebutuhan melalui diferensiasi konten, proses, produk, dan lingkungan belajar. Strategi pembelajaran diferensiasi dapat dikembangkan dengan mendiferensiasikan peserta didik berdasarkan golongan darah, genre musik, zodiak/weton jawa, grafologi, birth order, dan lainnya. Simpulan penelitian ini yaitu setiap peserta didik tidaklah sama dengan peserta didik yang lainnya, kemajemukan peserta didik tentunya sudah ada sejak lahiriah sehingga haruslah sesuai dengan kodrat alam dan kodrat zaman mereka maka diperlukan pembelajaran berdiferensiasi dalam Pendidikan.